(untitled) (Journal of Bangladesh Academy of Sciences, 2019)
The present study investigated the effects of salinity on the growth of groundnut (Arachis hypogaea L.), variety BARI Badam-8. The plants were grown in a series of plastic pots under controlled light and temperature conditions in the growth room. Salt (NaCl) solutions of different concentrations (0 mM, 50 mM, 100 mM, 150 mM, 200 mM, and 250 mM) were added to the pots, with three replicates. Results showed that shoot height, number of plants, main root length and lateral root length significantly decreased with the increase of salt concentrations. Fresh weight as well as dry weight of shoots and roots also decreased with the increase of salt concentrations while leaf proline and protein concentrations increased. Overall results indicate that high salinity condition is not suitable for growing groundnut. Journal of Bangladesh Academy of Sciences, Vol. 43, No. 1, 25-30, 2019